Total flavones of Rhododendron simsii Planch flower protect rat hippocampal neuron from hypoxia‐reoxygenation injury via activation of BKCa channel. (9th October 2019) - Guo, Yan; Yu, Xiao‐Meng; Chen, Shuo; Wen, Ji‐Yue; Chen, Zhi‐Wu
Abstract: Objectives: To study the effects of total flavones of Rhododendra simsii Planch flower (TFR) on hypoxia/reoxygenation (H/R) injury in rat hippocampal neurons and its underlying mechanism. Method: Model of H/R was established in newborn rat primary cultured hippocampal neuron. Lactate dehydrogenase (LDH) and neuron‐specific enolase (NSE) activity as well as malondialdehyde (MDA) content in cultured supernatants of the neurons were examined. Methyl thiazolyl tetrazolium assay and Hoechst33258 staining were, respectively, used to detect cell viability and apoptosis of neurons. Protein expression and current of BKCa channel were assessed by using Western blotting and whole‐cell patch‐clamp methods, respectively. Key findings: In the ranges of 3.7–300 mg/l, TFR significantly inhibited H/R‐induced decrease of neuronal viability and increases of LDH, NSE and MDA in the supernatants as well as apoptosis; TFR 33.3, 100 and 300 mg/l markedly increased current of BKCa channel rather than the BKCa channel protein expression in the neurons. Conclusions: Total flavones of R. simsii Planch flower had a protective effect against H/R injury in rat hippocampal neuron, and activation of BKCa channel may contribute to the neuroprotection.